(untitled) (International Scientific Conference Strategic Management and Decision Support Systems in Strategic Management, 2020)
Currently the national project "Labor productivity and employment support" is implementing in Russia a set of measures aimed at developing employment infrastructure and introducing organizational and technological innovations to support employment, including standard solutions aimed at improving the efficiency of state employment centers. This project defines the strategic directions of state regulation of the Russian labor market. This article deals with the issues of the population’s demand for the services of employment centers, including not only registering as unemployed but also receiving public services to assist in finding a suitable job, vocational training, psychological support, etc. The study is based on the Russian labor force survey and microdata of employment centers for 2019 (more than 24,000 observations). Based on the data from the labor force survey, there are drawn conclusions about the demand for the state employment centers’ services among various groups of the population and about typical combinations of applying to the employment service with other job search channels. The analysis of regional microdata made it possible to evaluate the performance of employment centers based on information about the socio-demographic characteristics of the unemployed, the duration of the unemployment status, the fact of receiving benefits, the services received and the reasons for de-registration. Based on the results of the analysis, there are made conclusions about the ways to improve the work of the state employment centers.